2014
DOI: 10.1155/2014/218295
|View full text |Cite
|
Sign up to set email alerts
|

Residual HEMA and TEGDMA Release and Cytotoxicity Evaluation of Resin-Modified Glass Ionomer Cement and Compomers Cured with Different Light Sources

Abstract: The purpose of this study was first to evaluate the elution of 2-hydroxyethyl methacrylate (HEMA) and triethylene glycol dimethacrylate (TEGDMA) monomers from resin-modified glass ionomer cement (RMGIC) and compomers cured with halogen and light-emitting diode (LED) light-curing units (LCUs). The effect of cured materials on the viability of L929 fibroblast cells was also evaluated. One RMGIC (Ketac N100) and two compomers (Dyract Extra and Twinkystar) were tested. Materials were prepared in teflon disks and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 41 publications
0
25
0
3
Order By: Relevance
“…These observations were related to the cement chemical compositions, in which ZP cements contain phosphoric acid, ZOE cements contain eugenol, and R cements are acrylate‐based, with these components being known skin irritants . Furthermore, studies have shown that R and RMGIC cements leach unreacted hydroxyethyl methacrylate (HEMA) and triethylene glycol dimethacrylate (TEGDMA) monomers and fluoride ions over a period of several weeks, which can lead to pulpal inflammation and cytotoxicity in preosteoblast and fibroblast cells . High concentrations of eugenol have long been associated with adverse inflammatory reaction, hypersensitivity, and cytotoxicity when in contact with soft‐tissue‐forming and osteoblastic cells .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations were related to the cement chemical compositions, in which ZP cements contain phosphoric acid, ZOE cements contain eugenol, and R cements are acrylate‐based, with these components being known skin irritants . Furthermore, studies have shown that R and RMGIC cements leach unreacted hydroxyethyl methacrylate (HEMA) and triethylene glycol dimethacrylate (TEGDMA) monomers and fluoride ions over a period of several weeks, which can lead to pulpal inflammation and cytotoxicity in preosteoblast and fibroblast cells . High concentrations of eugenol have long been associated with adverse inflammatory reaction, hypersensitivity, and cytotoxicity when in contact with soft‐tissue‐forming and osteoblastic cells .…”
Section: Discussionmentioning
confidence: 99%
“…38 Furthermore, studies have shown that R and RMGIC cements leach unreacted hydroxyethyl methacrylate (HEMA) and triethylene glycol dimethacrylate (TEGDMA) monomers and fluoride ions over a period of several weeks, which can lead to pulpal inflammation and cytotoxicity in preosteoblast and fibroblast cells. [39][40][41][42][43][44] High concentrations of eugenol have long been associated with adverse inflammatory reaction, hypersensitivity, and cytotoxicity when in contact with soft-tissue-forming and osteoblastic cells. 45,46 The observations of increased cytotoxicity for R, RMGIC, and ZOE cement compositions in this study can be related to these previous observations in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the high number of unreacted free monomers on deep dentin, even after hybrid layer formation, may induce oxidative stress, inflammatory mediator over-expression, depletion of anti-oxidant enzymes and alteration of dental pulp cell phenotypes. Consequently, apoptosis and necrotic cell death, as well as impaired regenerative potential, can be observed in pulp cells exposed to resin monomers (23).…”
Section: Properties Of Universal Adhesive Systemsmentioning
confidence: 99%
“…Lanza et al (4) identified HEMA in the culture medium in contact with MDPC-23 cells 24 h after the application of ASB and CSB to the occlusal sides of dentin discs. Studies have also demonstrated that HEMA is the main resin monomer capable of diffusing through dentin (23), since this monomer is responsible for promoting resin infiltration in deep demineralized dentin (9). It has been shown that this low-molecular-weight monomer is highly cytotoxic, causing pulp cell death mediated by oxidative stress and inhibiting cell phenotype expression related to healing (23).…”
Section: Properties Of Universal Adhesive Systemsmentioning
confidence: 99%
See 1 more Smart Citation